Silica Fertilizer (Si) Enhances Sugarcane Resistance to The Sugarcane Top Borer Scirpophaga excerptalis Walker - Rahardjo, Bambang Tri; Achadian, Etik Mar`ati; Taufiqurrahman, Achmad Fitriadi; Hidayat, Mohamad Rizkiy (AGRIVITA, Journal of Agricultural Science, 2021)
Sugarcane is an essential industrial that produce sugar in the world. Scirpophaga excerptalis attacks can reduce the productivity of sugarcane up to 34%. To enhance the resistance to multiple stresses, Silicon is one of the elements for its role. This research aimed to determine the effect of the provision of silica fertilizer as part of the Integrated Pest Management strategy. This research was conducted in the Plant Protection Department, Indonesian Sugar Research Institute. The compost given as treatment in this research was straw, cane, and corn composts. Organic silica fertilizer (compost) provides the same effect as inorganic silica fertilizer in increasing the induction of sugarcane resistance to sugarcane top borer (S. excerptalis). Rice straw compost was a compost fertilizer that provides the best sugarcane resistance to sugarcane top borer compared to sugarcane plants that treated with sugarcane and corn leave to compost